"The little things that I didn't see before": experience through gender stories and perceptions of feminism. (2nd January 2023) - Colley, Lauren M.; Krutka, Daniel G.
ABSTRACT: This socio-cultural practitioner-based study investigated the ways in which using a feminist pedagogy in a Gender and Education course would influence students' interpretations of their own lived experiences. Using atheory of experience, we examined reflections on 14 students' initial personal gender stories and their perceptions of feminism. At the end of the course, we examined the responses of these 14 students to their previously shared gender stories and feminism perceptions. Findings suggest that students were able to understand their experiences in historical and social contexts with regards to issues of gender equity, but also were less likely to place their experiences within the context of gender diversity and intersectionality. We argue that for students to understand their experiences within various identities and contexts that feminist educators must centre intersectionality, but also allow students to grow in their understandings of their experiences in their own ways. We contend that to do this, students need a curriculum that centres a critical and justice-oriented feminism and allows for experiences to be seen as discursive and contextual events.